Simulation of beam propagation in second-order nonlinear optical media - Al-Sunaidi, M. A. (2002)
Second-order nonlinearity in optical media acts as a source for harmonics generation. We set up a time-domain model that accounts not only for the second harmonic, but also for the higher harmonics that are induced by a beam propagation. The model is solved numerically using a second-order explicit scheme based on the exact solution of the nonlinear difference equation. The power spectrum of the generated harmonics is also presented.